SOME FEATURES OF PHAGOCYTIC CELL FUNCTIONS IN THE PATIENTS WITH MAXILLARY SINUSITIS SUFFERING FROM DIABETES MELLITUS - N. N. Popov; E. V. Ognivenko; E. A. Romanova (Медицинская иммунология, 2014)
Abstract. The study concerns phagocytic activity of neutrophilic granulocytes investigated in diabetic patients with insular diabetes, accompanied by maxillary sinusitis. The patients exhibited suppressed phagocytic abilities of neutrophilic granulocytes and monocytes, disturbed killing of captured bacteria, suppression of oxidase microbicidal system, and disorders of receptor system.